Analisis dan Perancangan User Interface Aplikasi Transaksi Pemesanan dan Pemasaran pada Kunokini Cafe & Resto Berbasis User Centered Design (UCD) - Heryawan Wisnuyana; Sulistiowati Sulistiowati; Nunuk Wahyuningtyas (Jurnal Sistem Informasi Universitas Dinamika, 2022)
KUNOKINI Cafe & Resto is a food and beverage business, located at Jalan Raya Prapen No. 69 Surabaya. KUNOKINI Cafe & Resto has been marketing its business using social media. Information available on KUNOKINI Cafe & Resto's social media includes company profile, location, prices, food/beverage menus, delivery orders (delivery), and place reservations (reservations). KUNOKINI Cafe & Resto is still recording customer data that wants to make a reservation in a notebook. Resulting in customers having to wait a long time for the reservation process. Based on this description, a user interface design has been carried out and produced a website prototype using a user centered design (UCD) approach. In the process of testing the prototype using usability testing methods to develop products as a benchmark for users. From the results of testing the prototype, the average value of 79.9% means that the design can be accepted by the user.